Edukasi Dampak Positif Bahan Organik bagi Keseimbangan Ekologi dalam Membangun Ekosistem Berkelanjutan - Agus Yadi Ismail; Sri Ayu Andayani; Suwari Akhmaddhian; Sukron Aminudin (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Activity aims to increase participants' understanding of the positive impact of organic matter on ecological balance and its application in sustainable agriculture. The workshop was carried out with a participatory education method involving 36 participants from six districts in West Java, through material presentations, interactive discussions, and simple demonstrations. Evaluation is carried out without a pretest and posttest, but through observation, interaction, and evaluation sheets with the categories of understanding level "very understanding", "understanding", and "not understanding". The results of the activity showed that 80% of the participants were in the category of very understanding, 15% in the category of understanding, and 5% in the category of not understanding. These findings indicate that the participatory workshop approach is effective in improving ecological literacy and participants' conceptual understanding of the importance of organic matter in maintaining soil and ecosystem health. This PKM has a positive impact in supporting the implementation of sustainable agricultural practices, as well as becoming an educational model that can be replicated in other regions with similar ecological problems.